ANALISIS PELAKSANAAN SUPERVISI AKADEMIK SEBAGAI UPAYA MENINGKATKAN MUTU PEMBELAJARAN OLEH PENGAWAS SEKOLAH DI SD NEGERI KOMPLEKS IKIP KOTA MAKASSAR - Wahyudi, Asril; Nursalam, Nursalam; Rosleny, Rosleny (Universitas Pakuan, 2021)
Analysis of the Implementation of Academic Supervision as an Effort to Improve the Quality of Learning by School Supervisors at Elementary Schools in the IKIP Complex in Makassar City This study uses a qualitative approach. The formulation of the research problem is (i) how are the objective conditions of the implementation of academic supervision by supervisors in improving the quality of learning at Elementary Schools in the IKIP Complex in Makassar City? (ii) how is the description of teacher professional competence in improving the quality of learning at Elementary Schools in the IKIP Complex in Makassar City? The purpose of this study is to describe the objective conditions of the implementation of academic supervision by supervisors in improving the quality of learning at Elementary Schools in the IKIP Complex in Makassar City, (ii) to describe the description of teacher professional competence in improving the quality of learning at Elementary Schools in the IKIP Complex in Makassar City. The results of this study indicate that the objective conditions of the implementation of academic supervision by supervisors in improving the quality of learning at Elementary Schools in the IKIP Complex in Makassar City are not optimal, seen from the results of informants who mostly said that supervisors had not allocated enough time to provide guidance to teachers. The professional competence of teachers in improving the quality of learning at the IKIP Complex Elementary School in Makassar City from the aspects of mastery of material, mastery of KI and KD, ability to develop teaching materials, and ability to utilize information technology in teacher learning have different levels.